Diaphragm degeneration and cardiac structure in mdx mouse: potential clinical implications for Duchenne muscular dystrophy. Issue 5 (29th January 2016) - Barbin, Isabel Cristina Chagas; Pereira, Juliano Alves; Bersan Rovere, Matheus; de Oliveira Moreira, Drielen; Marques, Maria Julia; Santo Neto, Humberto
Abstract: We examined the effects of exercise on diaphragm degeneration and cardiomyopathy in dystrophin‐deficient mdx mice. Mdx mice (11 months of age) were exercised (swimming) for 2 months to worsen diaphragm degeneration. Control mdx mice were kept sedentary. Morphological evaluation demonstrated increased fibrosis in the diaphragm of exercised mdx mice (33.3 ± 6.0% area of fibrosis) compared with control mdx mice (20.9 ± 1.7% area of fibrosis). Increased (26%) activity of MMP‐2, a marker of fibrosis, was detected in the diaphragms from exercised mdx mice. Morphological evaluation of the heart demonstrated a 45% increase in fibrosis in the right ventricle (8.3 ± 0.6% in sedentary vs. 12.0 ± 0.6% of fibrosis in exercised) and in the left ventricle (35% increase) in the exercised mdx mice. The density of inflammatory cells–degenerating cardiomyocytes increased 95% in the right ventricle (2.3 ± 0.6 in sedentary vs. 4.5 ± 0.8 in exercised) and 71% in the left ventricle (1.4 ± 0.6 sedentary vs. 2.4 ± 0.5 exercised). The levels of both active MMP‐2 and the pro‐fibrotic factor transforming growth factor beta were elevated in the hearts of exercised compared with sedentary mdx mice. The wall thickness to lumen diameter ratio of the pulmonary trunk was significantly increased in the exercised mdx mice (0.11 ± 0.04 in sedentary vs. 0.28 ± 0.12 in exercised), as was the thickness of the right ventricle wall, which suggests the occurrence of pulmonary hypertension in those animals. It is suggested that diaphragm degeneration is a main contributor to right ventricle dystrophic pathology. These findings may be relevant for future interventional studies for Duchenne muscular dystrophy‐associated cardiomyopathy.